The Postoperative Spine - Rankine, James J. (Seminars in Musculoskeletal Radiology, 2014)
Potential complications following spinal surgery include neural compression due to hematoma, recurrent disk herniation, epidural fibrosis, dural tear with pseudomeningocele formation, and infection. Specific complications relate to the use of spinal instrumentation that include incorrectly positioned instrumentation and failure of spinal fusion leading to instrumentation loosening or breakage. To interpret the postoperative imaging correctly, it is necessary to understand the nature of the surgical procedure that has been performed and the normal postoperative appearances. Magnetic resonance imaging is the mainstay in the evaluation of the postoperative spine. Radiographs and computed tomography continue to have a major role in assessing fusion and in the assessment of complications related to instrumentation.
Keywords: postoperative spine; epidural fibrosis; spinal instrumentation